Pengaruh Brand Image terhadap Purchase Intention Produk Le Minerale : dengan Peran Mediasi Social Influence - Fadya Al Yasha Syifa; Mirzam Arqy Ahmadi (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
The bottled water industry (AMDK) in Indonesia is highly competitive, requiring companies to develop effective marketing strategies. This study aims to analyze the influence of brand image on purchase intention for Le Minerale products, with social influence as a mediating variable. The research employs a quantitative survey method involving 100 respondents selected through purposive sampling. A Likert-scale questionnaire was used to measure respondents' perceptions of the study variables. Results analyzed using PLS-SEM indicate that brand image significantly impacts purchase intention, both directly and indirectly through social influence. A positive brand image enhances consumers' perception and trust in the product, while social influence strengthens this relationship. This study highlights the importance of brand image management and the role of social recommendations in influencing purchase decisions. However, limitations include the small sample size, potential respondent bias, and a lack of exploration of other factors such as price and product quality. Future research is recommended to expand population coverage, include additional variables, and adopt a longitudinal design.